Utilization of Methanol Extract Sea Pandan Fruit (Pandanus tectorius) in Hand and Body Cream as an Antioxidants - Dwi Retno Sari; Yusfia Urwatul Wutsqa; Siti Nur Hikmah (JURNAL FARMASI DAN MAKANAN, 2024)
Sea pandanus is a coastal plant with great potential in the cosmetic industry due to its rich contains phenolic and flavonoid compounds that are abundant in the fruits. The purpose of this research is determine the antioxidant activity of sea pandanus fruit and to evaluate the result of hand and body cream formulation. Pandanus was chosen because it is not widely explored.The result of study showed that the methanol extract of sea pandanus contains phenolic, flavonoid, saponin, and steroid compounds. The antioxidant activity in the hand and body cream formulation was 33,183 Âµg/mL, indicating strong antioxidant activity below the IC50. The high level antioxidant activity from the methanol extract of sea pandanus can be used in the formulation of hand and body cream. Characteristics in the quality assessment of all the hand and body cream did not meet the requirements.